Influence of Household Washing on the Colorimetric Properties of Intrinsically Natural Organic Cotton Fabrics - Hesam Aliei; Diana Cayuela; Francisco Javier Capdevila; Enric Carrera-Gallissà (Journal of Natural Fibers)
This research aimed to examine how household washing influences the colorimetric characteristics of natural colored organic cotton (NaCOC) fabrics. The colorimetric properties of (NaCOC) fabrics were assessed both before and after undergoing washing for up to 30 cycles. The findings indicated that washing significantly influenced the colorimetric properties of naturally dyed cotton fabrics, as evidenced by changes in lightness and saturation. The most significant difference in color between the two samples was observed after the initial wash, highlighting the reduction in both parameters, lightness and saturation, after this first washing. Between the second and fifth washes, there are notable differences in these parameters. However, from the fifth wash, the variation in color difference was minimal. Additionally, the FTIR-ATR analysis of the extracts in petroleum ether and subsequently in ethanol of the NaCOC fabrics, before and after home washing, in conjunction with a comparison with shrinkage, demonstrated that the latter process was accountable for the darkening of the sample.